Artificial Intelligence and Legal Transformation: Towards an Adaptive Justice System - Runik Erwanto; Richard Richard (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The development of artificial intelligence (AI) has had a major impact on various sectors, including the legal and judicial systems, which demand a transformation towards digitalization and efficiency. This research aims to analyze the contribution of AI in transforming conventional legal practices towards a more adaptive justice system, as well as examine the ethical, regulatory, and technological challenges that arise. This research uses a qualitative approach with literature studies as the main technique, reviewing literature, legal documents, and case studies of the application of AI in the judicial system in various countries. The findings show that AI is able to improve the efficiency and accuracy of legal processes, but its implementation still faces obstacles in terms of regulation, algorithm transparency, and institutional readiness. The transformation of the legal system through AI is inevitable, but it needs to be accompanied by regulatory reform, increased legal digital literacy, and the principle of prudence in its application in order to uphold substantive justice.